Implementasi Modul Inventory Menggunakan Odoo ERP pada Studi Kasus NMR Watch - Nitha Mahesya Rhani; Abdillah, Lufty (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Business systems, particularly those with influence in the information technology (IT) sector, have shown a great deal of huge effect in establishing and meeting the needs of company / business systems created to speed up the operations of organizations during the course of human history. NMR Watch is a corporation that makes and buys Watches of a certain kind for the express purpose of selling them to customers. Many players in the business process still rely on outmoded manuals, such as paper and digital jotters and spreadsheets, for tasks such as keeping track of stock product sales and purchases. Odoo ERP is the key data collecting platform for NMR Watch's operational operations, especially the Inventory module's function in establishing and monitoring product input and output data, therefore you'll need to help us with alpha and beta testing.